Social protection and gender: policy, practice and research - Hidrobo, Melissa; Peterman, Amber; Kumar, Neha; Lambon-Quayefio, Monica; Roy, Shalini; Gilligan, Daniel O.; Paz, Florencia (International Food Policy Research Institute, 2024)
Gender considerations in the design and delivery of social protection programs are critical to meet overall objectives of reducing poverty and vulnerability. We provide an overview of the policy discourse and research on social protection and gender in low- and middle-income countries, focusing on social assistance, social care, and social insurance. Taking a ‘review of reviews’ approach, we aggregate findings from rigorous evaluations on women's health, economic, empowerment, and violence impacts. We show there is robust evidence that social assistance has beneficial effects across all four domains. In addition, there is emerging evidence that social care has positive impacts on women’s economic outcomes, but scarce evidence of its impacts on other domains. Aggregated evidence on the impacts of social insurance are lacking. Key design elements facilitating positive impacts for women relate to gender targeting; quality complementary programming; replacing conditionalities with soft nudges; ensuring the value, frequency, and duration of benefits are sufficient; and gender-sensitive operational components. We close with a discussion of evidence gaps and priorities for future research.